Sistem Sistem Iot Untuk Pemantauan Suhu Dan Kelembaban Ruangan Secara Real-Time Sebagai Indikator Kualitas Udara - Sari, Melinda Novita; Sujono (Jurnal Ilmu Komputer dan Teknologi Informasi, 2026)
Indoor air quality is an important factor affecting human comfort, health, and productivity, especially in enclosed spaces with high usage intensity, where temperature and humidity serve as primary indicators of environmental conditions. This study aims to design and implement a real-time Internet of Things (IoT)-based temperature and humidity monitoring system using a DHT11 sensor and an ESP32 microcontroller integrated with the ThingSpeak cloud platform. The system is designed to collect environmental data, transmit it via a Wi-Fi network, and display the monitoring results in graphical form through a web dashboard. The research method includes hardware and software design, system implementation, and performance testing under normal indoor environmental conditions. The testing results indicate that the system is capable of displaying temperature and humidity data in real time with stable readings and deviations within the sensor’s tolerance limits, allowing consistent monitoring without significant interruptions. Practically, the system has potential applications in classrooms, offices, laboratories, and public facilities as a remote environmental monitoring solution. Furthermore, the system can be further developed by utilizing sensors with higher accuracy and incorporating additional air quality parameters to enhance its functionality and reliability.